PERANCANGAN SISTEM INFORMASI REGISTRASI MAHASISWA - Helpi Nopriandi (Universitas Islam Kuantan Singingi, 2018)
Implementation of appropriate information systems in universities can be a competitive power (competitive advantage) for universities to exist. Almost certainly this time, colleges that do not have a touch of information technology slowly but surely will be abandoned by prospective students. In this research methods in research reports that is data collection and direct observation on the processing of student registration information system as well as interviews with the administration that is still manual in processing student data. Therefore created a new information system using Visual Basic Program, This aims to address the problem of processing student registration information system at High School especially in the administration section, to obtain an advantage in providing information quickly and precisely in processing student data.